Intelligent lamp system / Norshahida Abd Karim - Abd Karim, Norshahida (2013)
Many people nowadays concern about the technology that can help or make their life easier especially at home. This project is about an Intelligent Lamp System, which capture an image using a LinkSprite JPEG Color Camera after receiving a signal from Long Analog Distance Sensor, process it, store the image and then turn LED on. A prototype of the lamp assistance system based on the proposed architecture was constructed here. The adopted hardware, software and implementation solutions in this prototype construction are described in this project. The effective image processing technique is used which is to convert hex code into a JPEG image. The design of home model by using AutoCAD and SketchUp software is also described in this project.